2008
DOI: 10.1007/s11557-008-0557-1
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of microsatellites in natural populations of ascomycetous fungus, Emericella nidulans, in Israel on local and regional scales

Abstract: The genetic divergence of Israeli populations of soil ascomycetous fungus Emericella nidulans was studied on regional and local scales using seven microsatellite (SSR) trinucleotide markers. The study was performed in the framework of the "Evolution Canyon" research program at the Institute of Evolution, University of Haifa, in three "Evolution Canyons" (EC): EC I (Mt. Carmel), EC II (western Upper Galilee), and EC III (the southern Negev desert). The first two canyons (EC I and EC II) are located in the north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Growth of the strains, DNA isolation, PCR amplification and statistical analysis were performed as it was described in our previous work (Hosid et al, 2005(Hosid et al, , 2008. The Spearman rank correlation test (StatSoft, 1996) was employed to estimate correlation between the variability of SSR markers (variance in repeat number) and physical distance from the markers to the centromere (% of chromosome arm length) (Table 1).…”
Section: (I) Sites Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Growth of the strains, DNA isolation, PCR amplification and statistical analysis were performed as it was described in our previous work (Hosid et al, 2005(Hosid et al, , 2008. The Spearman rank correlation test (StatSoft, 1996) was employed to estimate correlation between the variability of SSR markers (variance in repeat number) and physical distance from the markers to the centromere (% of chromosome arm length) (Table 1).…”
Section: (I) Sites Of Studymentioning
confidence: 99%
“…Previously, we studied the genetic variation of Israeli populations of E. nidulans on regional and local scales using seven microsatellite (simple sequence repeats or SSR) markers (Hosid et al, 2008). The study was performed in the framework of the ' Evolution Canyon ' research programme at the Institute of Evolution, University of Haifa, focusing on the effect of microscale environmental variability on biodiversity patterns (Nevo, 2001) in three ' Evolution Canyons' (ECs).…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that population performance is significantly related with genetic variation and natural selection which increase fitness of organism (Frankham, 2005). The ascomycete's soil fungus Emericella nidulans reveal high polymorphism in stress and arid environment when SSR markers applied (Hosid et al, 2008). Saleem et al (2001) also reported higher incidences of crossing over and gene conversion were in the strains isolated from SFS than strains from the NFS.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we studied the genetic divergence of Israeli populations of E. nidulans on regional and local scales using seven microsatellite markers (Hosid et al, 2008). The study was performed in three "Evolution Canyons" located in different Israeli regions in the framework of the "Evolution Canyon" research program at the Institute of Evolution, University of Haifa, focusing on the effect of microscale environmental variability on biodiversity patterns (Nevo, 2001).…”
Section: Microsatellite Diversity In Natural Populations Of Ascomycetmentioning
confidence: 99%
“…Carmel (EC I, 32º43¢N, 34º58¢E); Lower Nahal Keziv, western Upper Galilee Downloaded by [University of Reading] at 05:01 03 January 2015 (EC II, 33º02¢N, 35º11¢E), and Nahal Shaharut, the southern Negev desert (EC III,29º55¢N,34º58¢E). For detailed description of the canyons see Hosid et al (2008). EC I and EC II, located in the northern part of Israel, are characterized by sharply different microclimatic conditions (Pavliček et al, 2003).…”
Section: Sites Of Studymentioning
confidence: 99%